2023
DOI: 10.3390/pharmaceutics15112637
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Progress in the Role of Adipose-Derived Mesenchymal Stromal/Stem Cells in the Application of Central Nervous System Disorders

Haiyue Wu,
Yishu Fan,
Mengqi Zhang

Abstract: Currently, adipose-derived mesenchymal stromal/stem cells (ADMSCs) are recognized as a highly promising material for stem cell therapy due to their accessibility and safety. Given the frequently irreversible damage to neural cells associated with CNS disorders, ADMSC-related therapy, which primarily encompasses ADMSC transplantation and injection with exosomes derived from ADMSCs or secretome, has the capability to inhibit inflammatory response and neuronal apoptosis, promote neural regeneration, as well as mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Intraventricular injection of ADSCs has been shown to improve AD pathogenesis by modulating central cholesterol homeostasis [ 20 ]. A detailed review focusing on the role of ADSC-related therapy in CNS disorders is found elsewhere [ 21 ]. Adipose tissue-derived extracellular vesicles and microRNAs in obese patients and rodents cause synaptic loss and cognitive impairment [ 22 ].…”
Section: Remodeling Of Adipose Tissue Shapes Cognitive Functionmentioning
confidence: 99%
“…Intraventricular injection of ADSCs has been shown to improve AD pathogenesis by modulating central cholesterol homeostasis [ 20 ]. A detailed review focusing on the role of ADSC-related therapy in CNS disorders is found elsewhere [ 21 ]. Adipose tissue-derived extracellular vesicles and microRNAs in obese patients and rodents cause synaptic loss and cognitive impairment [ 22 ].…”
Section: Remodeling Of Adipose Tissue Shapes Cognitive Functionmentioning
confidence: 99%